(untitled) (Indian Journal of Nematology, 2024)
In present study, effect of various edaphic factors on spatial distribution of Meloidogyne spp in betel vine fields was analyzed statistically. Linear regression and path coefficient analysis quantified direct and indirect effects of the edaphic factors on nematode density. Soil pH (P = -0.727, á d” 0.05) was found to be negatively affecting the density of nematodes. Other edaphic factors such as, EC, P and Na showed significant correlation with nematode density. Path analysis and regression analysis enabled determination of hypothetical equations which could be sufficiently useful in determining the most suitable selection factor for nematode abundance.